2017
DOI: 10.21815/jde.017.095
|View full text |Cite
|
Sign up to set email alerts
|

Developing Prosthodontic Residents’ Communication Strategies with Edentulous Patients: A Pilot Study

Abstract: The aim of this study was to investigate whether prosthodontic residents' attitudes toward provider-client communication would be shaped by a tailor-made communications skills course. In 2016, the pre-intervention attitudes of all six second- and third-year prosthodontic residents in a three-year residency at an academic dental institution in India were assessed using the Communication Skills Attitude Scale (CSAS). The residents' performance was then video-recorded while they treated complete denture patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The individualized feedback dealt with telling the postgraduates their specific strength and weakness in communication skills, as observed in the videorecordings. 1 The immediate open feedback regarding the training program revealed that the postgraduates wanted regular feedback on their performance posttraining. Due to the interest shown by them, it was decided to continue video recording their interactions with another set of 66 complete-denture patients for observing continuation or decay of the application of the skills taught.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The individualized feedback dealt with telling the postgraduates their specific strength and weakness in communication skills, as observed in the videorecordings. 1 The immediate open feedback regarding the training program revealed that the postgraduates wanted regular feedback on their performance posttraining. Due to the interest shown by them, it was decided to continue video recording their interactions with another set of 66 complete-denture patients for observing continuation or decay of the application of the skills taught.…”
Section: Methodsmentioning
confidence: 99%
“…It is hardly taught systematically in dental training and is learned from role models or seniors as a hidden curriculum. 1 The training programs on doctor-patient communication may vary, depending on the depth of the subject/skills covered. However, such programs may not serve the purpose unless there is the engagement of learners and follow up on the application of the skills taught.…”
Section: Introductionmentioning
confidence: 99%
“…7 These simulation formats may be completed by video-recording analysis previously developed for postgraduate residents in order to develop their communication skills. 8 Before 2019, undergraduates enrolled at the University of Paris benefited from lectures dealing with knowledge, and practical works focusing on clinical and laboratory procedural skill training with or without phantom head simulators, at the preclinical level. Clinical practice under the supervision of a senior practitioner was also proposed to students during their internship.…”
Section: Introductionmentioning
confidence: 99%
“…Several simulation formats may be proposed to undergraduate students for technical procedures learning of complete denture provision, including phantom head simulators 6 and standardized patients 7 . These simulation formats may be completed by video‐recording analysis previously developed for postgraduate residents in order to develop their communication skills 8 . Before 2019, undergraduates enrolled at the University of Paris benefited from lectures dealing with knowledge, and practical works focusing on clinical and laboratory procedural skill training with or without phantom head simulators, at the preclinical level.…”
Section: Introductionmentioning
confidence: 99%